Synthesis and Photophysical Properties of 1,4-Dihydro-2H,5H-chromeno[4,3-d][1,3]oxazin-5-ones, and Derivatives Containing Tethered 1,2,3-Triazoles, from 4-Aminocoumarins - Dilelio, Marina C.; Brites, Nathan P.; Vieira, Larissa A.; Iglesias, Bernardo A.; Kaufman, Teodoro S.; Silveira, Claudio C. (Synthesis, 2019)
A facile protocol for the unprecedented one-pot H2SO4-mediated hydroxymethylation/cyclative N,O-acetalization of 4-aminocoumarins to 1,4-dihydro-2H,5H-chromeno[4,3-d][1,3]oxazin-5-ones, in moderate to good yields, was developed and optimized. The scope and limitations of the transformation, which takes place in water or water/THF mixtures, were also studied. The nitrogen atom of the resulting tricycles was used to tether alkyl, aryl and 1,2,3-triazolylmethyl moieties, employing a two-step click chemistry approach for the latter. The photophysical properties of the heterocycles, as well as of their 1,2,3-triazole derivatives, were also examined. The N-aryl derivatives exhibited high quantum yields of fluorescence (up to Φf = 0.69) and very large Stokes shifts (up to 201 nm).
Keywords: 4-aminocoumarins; tethered triazoles; 1,3-oxazines; cyclization reaction; photophysical properties